Effects of a Rhodiola rosea extract on mental resource allocation and attention: An event‐related potential dual task study. (27th June 2020) - Koop, Tina; Dienel, Angelika; Heldmann, Marcus; Münte, Thomas F.
Abstract : Rhodiola rosea extract is widely used to alleviate stress and improve cognition and mental resources. A total of 50 adult participants were treated with 2 × 200 mg R. rosea extract (Rosalin®, WS® 1, 375) for 12 weeks and were subjected to a neuropsychological test battery as well as an event‐related brain potential measurement in a dual task paradigm prior to administration, after 6 weeks and after 12 weeks. The study followed a single‐arm open‐label design. Reaction times improved for the attention network task (ANT), the Go/Nogo task, and the divided attention task. Moreover, the orienting effect and the executive effect in the ANT showed an improvement. The P3 component in a dual task paradigm was increased in amplitude. The results of this pilot study show an improvement of mental speed and moreover, suggest improved mental resources. As the current study is single‐armed these findings need to be replicated in a double‐blind placebo controlled study.